Clinical Epidemiology & Evidence-Based Medicine : Fundamental Principles of Clinical Reasoning and Research. - Katz, Dr. David L. (SAGE Publications, 2001)
"The presentation is consistently excellent. One, the writing is lucid and organized in a way that should be very natural for the clinical reader. Two, the text requires no background in mathematics and uses a minimum of symbols. And, three, the methodological concepts and clinical issues are well integrated through a number of carefully prepared and comprehensive examples." Greg Samsa, Associate Director, Duke Center for Clinical Health Policy Research If a patient is older or younger than, sicker or healthier than, taller or shorter than or simply different from the subjects of a st.